2011
DOI: 10.1051/0004-6361/201016402
|View full text |Cite
|
Sign up to set email alerts
|

The puzzling deuteration of methanol in low- to high-mass protostars

Abstract: Context. The current theory of methanol deuteration on interstellar grains predicts that the abundance ratio of the singly deuterated isotopologues [ OD] ratios are inconsistent with the current theory of methanol deuteration, independently of the mass of the source. While the large ratios measured in low-and intermediate-mass sources can be explained qualitatively by various selective depletion mechanisms, the small ratios (<2) measured toward massive hot cores are puzzling. A revision of the deuterium chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 21 publications
4
57
1
Order By: Relevance
“…(A4) of Caselli et al (2002) from one transition only assuming optically thin conditions and adopting the rotation temperature derived from CH 3 OH, available in all sources as excitation temperature. The partition functions of all species have been calculated from the approximated expressions valid for asymmetric rotors provided, e.g., in Ratajczak et al (2011;see also Parise 2004). The results of this analysis are presented in Table 8.…”
Section: Derivation Of Molecular Column Densities and Rotation Tempermentioning
confidence: 99%
“…(A4) of Caselli et al (2002) from one transition only assuming optically thin conditions and adopting the rotation temperature derived from CH 3 OH, available in all sources as excitation temperature. The partition functions of all species have been calculated from the approximated expressions valid for asymmetric rotors provided, e.g., in Ratajczak et al (2011;see also Parise 2004). The results of this analysis are presented in Table 8.…”
Section: Derivation Of Molecular Column Densities and Rotation Tempermentioning
confidence: 99%
“…This is used to determine the formation pathway as shown by Cazaux et al (2011) and Coutens et al (2012), with the formation of water and formaldehyde. However, the process could be similar for hot cores, as shown by Turner (1990) or recently by Ratajczak et al (2011). Therefore we recently made extensive laboratory measurements to be able to search for the millimeter-wave spectrum of D-isotopologues of glycolaldehyde in the ISM.…”
Section: Introductionmentioning
confidence: 99%
“…For methanol the abundance ratio of the deuterated isotopologues, [CH 2 DOH]/[CH 3 OD], is predicted to be about three (Charnley et al 1997). However, this ratio has been observed to lie in the range 5 to 30 towards low-mass and intermediate protostars (Parise et al 2006;Ratajczak et al 2011) and close to or below one in high-mass protostars (Ratajczak et al 2011). Recent laboratory studies (Nagaoka et al 2005;Ratajczak et al 2009) have shown that a much lower abundance of CH 3 OD than for CH 2 DOH, as observed in low-and intermediate-mass protostars (Ratajczak et al 2011), can be qualitatively explained via H/D exchanges occurring on the grain surface following methanol formation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in the case of formamide, DCONH 2 species should be significantly more abundant than HCONDH and HCONHD ones, if solid H/D exchanges do happen, because these should take place on the amino group -ND 2 . On the other hand, the three deuterated isotopologues of formamide could have a similar abundance owing to some alternative or additional mechanisms in the postevaporative gas phase, as discussed for methanol by Ratajczak et al (2011). A&A 549, A128 (2013) Formamide is a small molecule with relatively light molecular weight (M = 44) and with non-zero μ a = 3.62 D and μ b = 0.85 D dipole moment components (Kurland & Wilson 1957).…”
Section: Introductionmentioning
confidence: 99%